The Impacts of the Physiological Changes Occurring During Pregnancy on Pharmacokinetic Mechanisms - AKICI, AHMET; GÖREN, MEHMET ZAFER (MARMARA UNIV, INST HEALTH SCIENCES, 2017)
Although pharmacotherapy is avoided due to risks during pregnancy, sometimes drugs may be required for specific clinical conditions. Inappropriate use because of limited available information may lead to malpractice. Health professionals, especially physicians, should have a better knowledge of the fact that drug use in pregnant women has some important differences from that in normal adults. Thus, they must comply with these specific requirements. One of the major differences is the change in drug pharmacokinetics during pregnancy. Important changes related to drug absorption, distribution, metabolism, and elimination show wide variability in maternal body, placenta, embryo, and fetus. These changes determine the selection of drug, its dose, and duration of its use. The successful management of treatment process during pregnancy is difficult and sometimes requires professional support due to confounding reasons, including individual factors, gestational age, mothers' age, and underlying diseases and their impact on drug metabolism. Therefore, health professionals and patients are required to get better benefit from sources, especially from clinical pharmacology information services. The present review discusses the details of how and to what extent the pharmacokinetic mechanisms are affected by the physiological changes that occur during pregnancy and their interpretation to clinical conditions.
Keywords: Gestation; pharmacokinetics; maternal; physiological changes; placental transfer; CYP2D6